Google Forms як ефективний засіб для проведення онлайн-опитувань - Єршова, Анастасія; Федушко, Соломія; Сєров, Юрій (Видавництво Львівської політехніки, 2019)
This article provides information on the ease using of Google forms for creating a survey, functional advantages and disadvantages, a direct link to the combination of information graphics. The main attention is paid to the creation of a successful structured form for future distribution among people. The peculiarities of creating questions, their screwed functionality, general design of the form are highlighted.
Keywords: інформаційна графіка; опитування; Google forms; анкетування